2010
DOI: 10.1007/s12098-010-0046-9
|View full text |Cite
|
Sign up to set email alerts
|

Developmental profile in children with iron deficiency anemia and its changes after therapeutic iron supplementation

Abstract: Children with IDA have suboptimal developmental scores. The delayed development is variably reversible following oral iron therapy. Hb =< 7 g/dl and age >24 months predicts suboptimal outcome. FMD is a useful method of interpreting DPII.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 19 publications
(25 reference statements)
1
13
0
1
Order By: Relevance
“…The study revealed that maximum cases were found in the age group of 6months to 3 years which is in concordance with observation made by various workers [16][17][18][19]. Considering the peculiar circumstances of diet, period of rapid and variable growth, lack of immunity and increased susceptibility to infections and effects of other extraneous influences on the haemopoietic system, anemia is quite common in infancy and early childhood.…”
Section: Discussionsupporting
confidence: 88%
“…The study revealed that maximum cases were found in the age group of 6months to 3 years which is in concordance with observation made by various workers [16][17][18][19]. Considering the peculiar circumstances of diet, period of rapid and variable growth, lack of immunity and increased susceptibility to infections and effects of other extraneous influences on the haemopoietic system, anemia is quite common in infancy and early childhood.…”
Section: Discussionsupporting
confidence: 88%
“…Studies indicate high correlations with the IQ calculated from DP II and from other conventional measures. The DP II has been used to measure the intelligence of children in India (Gupta et al 2010;Malhi and Singhi 2003;Malhi et al 2006).…”
Section: Methodsmentioning
confidence: 99%
“…Anemia in infancy and early childhood is also associated with delayed development especially behavioural and cognitive delay and impaired learning and mental skills. A study by Gupta et al showed that children with iron deficiency anemia had suboptimal development score and this delayed development was variably reversible following iron therapy [15].…”
Section: Original Research Articlementioning
confidence: 99%